Artificial intelligence and firm growth — catch-up processes of SMEs through integrating AI into their knowledge bases - Alexander Kopka; Dirk Fornahl (Small Business Economics, 2023)
Artificial intelligence (AI) is seen as a key technology for future economic growth. It is labelled as a general-purpose technology, as well as an invention of a method for inventing. Thus, AI is perceived to generate technological opportunities and through these, innovations, and productivity growth. The leapfrogging hypothesis suggests that latecomer firms can use these opportunities to catch up. The aim of this paper is to provide insight into this catch-up process of latecomer firms through integrating AI into their knowledge portfolio and thereby creating new technological trajectories. The moderating effect of firm size is also analysed. Combining firm-level data with patent data, a regression at the firm level is conducted. Evidence is found that smaller firms experience productivity growth from AI when operating at the productivity frontier, indicating the opposite of the leapfrogging hypothesis. However, there is evidence for the positive impact of AI on firm innovation, which is higher for latecomer firms that are larger in size. In general, we find a diverging pattern of the influence of AI on productivity and innovation growth, indicating the need for a finer grained analysis that takes indirect effects - that also could explain the observed productivity paradox - into account.
Keywords: O31; O32; O33; O47; L25; 330; Artificial intelligence; Firm growth; Catch-up; Innovation; Productivity